KEPEMIMPINAN MOTIVASI DAN KOMPENSASI PENGARUHNYA TERHADAP KINERJA (STUDI PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA LUBUKLINGGAU SUMATERA SELATAN) - Yohanes Susanto; Hendrik Hendrik (LPPM UNIVERSITAS BINA INSAN, 2020)
This study aims to examine the effect of leadership, motivation and compensation on employee performance at the local tax and retribution management body in Lubuklinggau City, with a sample of 38 respondents from employees. shows, partially there is a positive and significant influence of each exogenous variable on the endogenous variables, namely the variables of leadership, motivation and compensation have an effect on employee performance, and simultaneously the four exogenous variables jointly affect employee performance. However, partially the compensation variable is more dominant in influencing employee performance. Management implication, that either simultaneously or partially each variable affects employee performance, however the most dominant variable compensation is therefore it is suggested that management pay attention to the compensation structure in order to improve performance.